Biosorption kinetic models on the removal of Congo red onto unripe calamansi (Citrus microcarpa) peels - Sumalapao, Derick Erl P. (Animo Repository, 2016)
Unripe calamansi peels were prepared and used as a bioadsorbent in the removal of congo red from an aqueous solution using batch adsorption studies. The efficiency of adsorption was evaluated by varying adsorbent dose and contact time. The removal of congo red increased at higher adsorbent dose and longer contact time. The overall rate of adsorption processes appeared to be in accordance with the pseudo-second order reaction mechanism. Higher initial adsorption rate, extent of surface coverage, and activation energy were favored at a lower adsorbent dose, while the intraparticle diffusion was relatively faster at a higher adsorbent dose. The intraparticle diffusion, Elovich, and MacArthur-Wilson models were adequate in describing the chaotic behavior of the kinetic processes involved in the removal of congo red dye onto unripe calamansi peels. © 2016, Oriental Scientific Publishing Company. All rights reserved.